The Better-Than-Average Effect Is Observed Because “Average” Is Often Construed as Below-Median Ability - Kim, Young-Hoon (Front Psychol, 2017)
Most people rate their abilities as better than “average” even though it is statistically impossible for most people to have better-than-median abilities. Some investigators explained this phenomenon in terms of a self-enhancement bias. The present study complements this motivational explanation with the parsimonious cognitive explanation that the phrase “average ability” may be interpreted as below-median ability rather than median ability. We believe people tend to construe an “average” target that is based on the most representative exemplar, and this result in different levels of “average” in different domains. Participants compared their abilities to those of an average person, typical person, and a person whose abilities are at the 40th, 50th, or 60th percentile. We found that participants’ interpretation of “average” ability depended on the perceived difficulty of the ability. For abilities perceived as easy (e.g., spoken and written expression), participants construed an “average” target at the 40th percentile (i.e., below-median ability) and showed a marked better-than-average effect. On the contrary, for abilities perceived to be difficult, participants construed an “average” target at the median or even above the median.